Large-Scale Assembly of Peptide-Based Hierarchical Nanostructures and Their Antiferroelectric Properties - Lee, Yonghun; Kim, Kyung Won; Duong, Nguyen Xuan; Park, Hyeok; Park, Jinhong; Ahn, Chang Won; Park, In Woo; Jang, Seok Cheon; Kim, Dong Hoe; Lee, Minbaek; Chung, Woo Jae; Kim, Tae Heon; et al. (Small, 2020)
An effective strategy is developed to create peptide-based hierarchical nanostructures through the meniscus-driven self-assembly in a large area and fabricate antiferroelectric devices based on these nanostructures for the first time. The diphenylalanine hierarchical nanostructures (FF-HNs) are self-assembled by vertically pulling a substrate from a diphenylalanine (FF) solution dissolved in a miscible solvent under precisely controlled conditions. Owing to the unique structural properties of FF nanostructures, including high crystallinity and α-helix structures, FF-HNs possess a net electrical dipole moment, which can be switched in an external electric field. The mass production of antiferroelectric devices based on FF-HNs can be successfully achieved by means of this biomimetic assembly technique. The devices show an evident antiferroelectric to ferroelectric transition under dark conditions, while the ferroelectricity is found to be tunable by light. Notably, it is discovered that the modulation of antiferroelectric behaviors of FF-HNs under glutaraldehyde exposure is due to the FF molecules that are transformed into cyclophenylalanine by glutaraldehyde. This work provides a stepping stone toward the mass production of self-assembled hierarchical nanostructures based on biomolecules as well as the mass fabrication of electronic devices based on biomolecular nanostructures for practical applications.
Keywords: Anti ferroelectrics; Antiferroelectric properties; Biomimetic assemblies; Controlled conditions; External electric field; Ferroelectric transition; Hierarchical Nanostructures; High crystallinity; Electricity; Nanostructures; Peptides; Solvents; aldehyde detection; antiferroelectric devices; diphenylalanine; hierarchical nanostructures; self-assembled nanostructures